2019
DOI: 10.3390/catal9070589
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hollow Flower-Like Fe3O4/MnO2/Mn3O4 Magnetically Separable Microspheres with Valence Heterostructure for Dye Degradation

Abstract: In this manuscript, hollow flower-like ferric oxide/manganese dioxide/trimanganese tetraoxide (Fe3O4/MnO2/Mn3O4) magnetically separable microspheres were prepared by combining a simple hydrothermal method and reduction method. As the MnO2 nanoflower working as precursor was partially reduced, Mn3O4 nanoparticles were in situ grown from the MnO2 nanosheet. The composite microspheres were characterized in detail by employing scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this work, we present an atomic resolution live (in-situ) study of electron beaminduced transformations in core/shell Fe3O4/Mn3O4 and Mn3O4/Fe3O4 nanoparticles by means of high-resolution scanning transmission electron microscopy combined with electron energy-loss spectroscopy (STEM-EELS). Interestingly, the manganese oxideiron oxide nanoparticles system is appealing not only for its unique magnetic properties (e.g., antiferromagnetic interface coupling or magnetic proximity effects) [10,[38][39][40] but also for its applications in diverse fields like catalysis and environmental remediation [41,42], batteries and supercapacitors [43,44], microwave components [45] or biomedicine [46,47]. Our results, acquired within time scale of minutes, show that the nanoparticles under electron irradiation can develop a variety of defects, including formation of voids and dislocations, as the Mn3O4 component is forced to reduce to MnO.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present an atomic resolution live (in-situ) study of electron beaminduced transformations in core/shell Fe3O4/Mn3O4 and Mn3O4/Fe3O4 nanoparticles by means of high-resolution scanning transmission electron microscopy combined with electron energy-loss spectroscopy (STEM-EELS). Interestingly, the manganese oxideiron oxide nanoparticles system is appealing not only for its unique magnetic properties (e.g., antiferromagnetic interface coupling or magnetic proximity effects) [10,[38][39][40] but also for its applications in diverse fields like catalysis and environmental remediation [41,42], batteries and supercapacitors [43,44], microwave components [45] or biomedicine [46,47]. Our results, acquired within time scale of minutes, show that the nanoparticles under electron irradiation can develop a variety of defects, including formation of voids and dislocations, as the Mn3O4 component is forced to reduce to MnO.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the binding energy of Mn 4+ ions in MnO 2 for the Mn 2p 3/2 level is at 642.4–642.8 eV, while the lower oxidation states of Mn 2 O 3 , Mn 3 O 4 and MnO are located in the range of 640.8–641.6 eV [39] . Therefore, the three pairs of doublets with the doublet at 640.9/652.7 eV, 641.8/653.7 eV, and 642.9/654.6 eV can be ascribed to the Mn 2+ , Mn 3+ , and Mn 4+ according to the reported work, implying that the as‐synthesized ZnMM‐NSs sample contains multivalent state manganese (Mn(II), Mn(III), and Mn(IV)) [40–41] . In addition, the energy separation between two peaks of Mn 3 s core level spectrum can be used to determine the mean manganese oxidation state of manganese oxides [22] .…”
Section: Resultsmentioning
confidence: 54%
“…[39] Therefore, the three pairs of doublets with the doublet at 640.9/652.7 eV, 641.8/653.7 eV, and 642.9/654.6 eV can be ascribed to the Mn 2 + , Mn 3 + , and Mn 4 + according to the reported work, implying that the assynthesized ZnMM-NSs sample contains multivalent state manganese (Mn(II), Mn(III), and Mn(IV)). [40][41] In addition, the energy separation between two peaks of Mn 3 s core level spectrum can be used to determine the mean manganese oxidation state of manganese oxides. [22] The peak separation is 5.16 eV (Figure 3c), suggesting that the Mn oxidation states of as-prepared ZnMM-NSs is ca.…”
Section: Chemelectrochemmentioning
confidence: 99%